VD_FINDINFO HC / 2014 / 413 vom 16. Mai 2014 - VD Tribunal cantonal (2014)
CONDITION DE RECEVABILITÉ, COMPÉTENCE, TRANSMISSION D'UN ACTE PROCÉDURAL | 96 LOJV, 237 CPC (CH), 319 let. a CPC (CH), 59 CPC (CH), 63 CPC (CH)